(untitled) (Tạp chí Y học Cộng đồng, 2025)
Objective: Describe the knowledge about cerebral stroke prevention among hypertensive patients at Ninh Binh Provincial General Hospital in 2023. Methods: A cross-sectional descriptive study was conducted on 222 hypertensive patients managed at the Cardiovascular Clinic, Examination Department, Ninh Binh Provincial General Hospital from March 2023 to June 2023.. Results: Over 90% of patients knew the common symptoms and prevention of stroke. However, only 44.1% of patients reported that sudden memory loss was a sign of stroke. 69.4% of patients had good knowledge, while 30.6% had poor knowledge about stroke prevention. Patients with a higher education level had better knowledge about stroke prevention than those with a lower education level, Conclusion: Stroke prevention in hypertensive patients was significant in improving health and quality of life, reducing the incidence of other chronic diseases, so it is necessary to strengthen health education for patients.